AMPD1 polymorphism and response to regadenoson. (November 2015) - Saab, Rayan; Zouk, Aline N; Mastouri, Ronald; Skaar, Todd C; Philips, Santosh; Kreutz, Rolf P
Aims:   AMPD1 c.34C > T (rs17602729) polymorphism results in AMPD1 deficiency. We examined the association of AMPD1 deficiency and variability of hemodynamic response to regadenoson.Subjects & methods: Genotyping for c.34C>T was performed in 267 patients undergoing regadenoson cardiac stress testing.Results: Carriers of c.34C >T variant exhibited higher relative changes in systolic blood pressure (SBP) compared with wild-type subjects ([%] SBP change to peak: 12 ± 25 vs 5 ± 13%; p = 0.01) ([%] SBP change to nadir: -3 ± 15 vs -7 ± 11%; p = 0.04). Change in heart rate was similar between groups, but side effects were more common in carriers of the variant (+LR = 4.2; p = 0.04).Conclusion: AMPD1 deficiency may be involved in the modulation of regadenoson's systemic effects.